Pengaruh Kerelasian Pelanggan, Kualitas Pelayanan dan Harga terhadap Nilai Pelanggan serta Implikasinya pada Loyalitas Pelanggan - Pebi Kurniawan (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2016)
The purpose of this study was to analyze the influence of relations of customer, service quality and price of customer value and customer loyalty, and the influence of relations customer, service quality and price of customer value, also the effect of customer value on customer loyalty. The method used is descriptive and verification with simple technique by using stratifield random sampling on 568 congregation. The data was analyzed using Path analysis techniques (Path Analysis). The results indicate that: Relations Customer was pretty good towards good, The quality of service was good enough towards good service, The price was quite good towards good, Customer Value was well enough for good, Loyalty Customers good enough towards either there was different significan either partially or simultaneously from the variable of customer relations, service quality and the price of customer Value, there was a strong influence of Customer Value on Customer Loyalty.